2019
DOI: 10.7150/jca.33244
|View full text |Cite
|
Sign up to set email alerts
|

High expression of DOCK2 indicates good prognosis in acute myeloid leukemia

Abstract: DOCK family proteins are evolutionarily conserved guanine nucleotide exchange factors for Rho GTPase with different cellular functions. It has been demonstrated that DOCK1 had adverse prognostic effect in acute myeloid leukemia (AML). We first analyzed data of 85 AML patients who were treated with chemotherapy and had available DOCK1 to DOCK11 expression information and found that DOCK1 and DOCK2 had prognostic significance in AML. In view of the known prognosis of DOCK1 in AML, we then explored the prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It can also regulate the functions of innate immune cells such as the migration and interferon (IFN) secretion of plasmacytoid dendritic cells, the cytotoxicity of natural killer (NK) cells, and the reactive oxygen species (ROS) production of neutrophils ( Chen et al, 2018b ). DOCK2 mutations have been observed in many cancers, including chronic lymphocytic leukemia (CLL), prostate cancer, and acute myeloid leukemia (AML; Hasan et al, 2018 ; Bjerre et al, 2019 ; Hu et al, 2019 ). In particular, DOCK2 might be a potential druggable target for AML with FLT3/internal tandem duplication (ITD) mutations ( Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can also regulate the functions of innate immune cells such as the migration and interferon (IFN) secretion of plasmacytoid dendritic cells, the cytotoxicity of natural killer (NK) cells, and the reactive oxygen species (ROS) production of neutrophils ( Chen et al, 2018b ). DOCK2 mutations have been observed in many cancers, including chronic lymphocytic leukemia (CLL), prostate cancer, and acute myeloid leukemia (AML; Hasan et al, 2018 ; Bjerre et al, 2019 ; Hu et al, 2019 ). In particular, DOCK2 might be a potential druggable target for AML with FLT3/internal tandem duplication (ITD) mutations ( Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DOCK2 plays a critical role in the modulation of the immune system [56]. Hu et al [57] have reported that low expression of DOCK2 is associated with poorer prognosis of acute myeloid leukemia. Recent study reported that DOCK2 hypermethylation was associated with biochemical recurrence after radical prostatectomy in prostate cancer [58].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, DOCK2 belonging to the Rho GEFs family activates GTPase which has the opposite function compared with Rho GAPs. Also, it was an independent favorable prognostic factor for both EFS and OS in AML [40]. Thus, in addition to being associated with GTPase, some regulators of Rho GTPase may have other functions in cancer.…”
Section: Discussionmentioning
confidence: 94%